Deposit Insurance Agency Between Legal Protection and Banking Crime - Mambaya, Marthinus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research was conducted with the aim of, among other things, wanting to know, understand and explain the role of deposit insurance institutions between legal protection and banking crime. To obtain accurate and scientifically accountable data, normative and empirical juridical research methods are used. The research results reveal that banking transactions are something that should be prioritized so that the interests of the parties can be protected. In law enforcement, these pairs of values need to be harmonized and explained more concretely because these values are usually abstract. Suggestions for utilizing legal tools for bank fraud are carried out using various modus operandi, in the form of deviation from Bank Indonesia Liquidity Assistance (BLBI) by disbursing it in the form of fictitious credit and bank balance mark-ups. Bank Indonesia has a big responsibility to protect and guarantee clients from losses caused by wrong bank actions as the institution that forms and supervises the banking system in Indonesia. To ensure that all banks operating in Indonesia implement statutory provisions, Bank Indonesia must be more active in carrying out its duties and authorities. Good and effective supervision helps reduce client losses due to bank actions.